Los diputados renovadores. De la XXVI Legislatura al Congreso Constituyente - MacGregor, Josefina (El Colegio de México, A.C., 2017)
A group known as “renovating” is alluded to during the Constituent Congress as well as in the work produced by participating representatives. The adjective “renovating” stemmed from the XXVI Legislature of 1912-1913. This article follows the trajectory of these representatives, from Madero’s government up to the 1916-1917 Congress. It is intended to show that, while these legislators had a broad participation in the Constituent Congress, they did not represent a defined political group, and the term “renovating” was circumscribed to a small circle made up mainly by José N. Macías, Luis Manuel Rojas, Alfonso Cravioto, Félix F. Palavicini and Gerzayn Ugarte who, as Venustiano Carranza’s collaborators, had participated in the draft for the Constitution. However, these circumstances do not suffice to explain their behaviour when debating objections and voting reforms to different articles of the Draft.